Analysis Of The Authority of the Notary and Legal Security Towards the Transfer of Property Rights to Grant Land - Muhamad Abdul Azis; Benny Djaja (PT Publikasiku Academic Solution, 2023)
In the process of transferring rights, both inheritance and grants, in field conditions there are always problems or obstacles that result in the process of suspending the transition. Based on this phenomenon, the aim of the research is to find out the authority of a notary regarding the ownership of grant land parcels and to find out the legal certainty of an authentic notary deed in the transfer of property rights. Over Land grants. This research is normative juridical research that is qualitative in nature. The type of data used is secondary data, in this study the data analysis used is qualitative analysis. The results of the research show that the transfer of grant rights must be stated in a deed made by a notary / PPAT who is given authority as a public official by law as an authentic deed maker. a grant deed made by a notary/PPAT has legal certainty because it has concrete legal force, with the existence of the deed, both the grantor and the recipient of the grant are protected by applicable law. UUJN makes an authentic deed, related to the transfer of grant rights where evidence of an object that has been donated must be proven by an authentic deed made, witnessed and signed by a notary/PPAT is a legal certainty for the parties giving and receiving grants